Volatile compounds in health and disease - Španěl, Patrik; Smith, David (Current opinion in clinical nutrition and metabolic care, 2011)
PURPOSE OF REVIEW: To summarize the recent progress made in noninvasive monitoring of volatile compounds in exhaled breath and above biological liquids, as they are becoming increasingly important in assessing the nutritional and clinical status and beginning to provide support to conventional clinical diagnostics and therapy. To indicate the potential of these developments in medicine and the specific areas which are currently under investigation. RECENT FINDINGS: The significance of the following breath gases and their concentrations are reported: acetone and the influence of diet; ammonia confirmed as an indicator of dialysis efficacy; hydrogen and the (13)CO(2)/(12)CO(2) ratio (following the ingestion of (13)C-labeled compounds) as related to gastric emptying and bowel transit times; hydrogen cyanide released by Pseudomonas and its detection in breath of children with cystic fibrosis; and multiple trace compounds in breath of patients with specific pathophysiological conditions and 'metabolic profiling'. SUMMARY: Advanced analytical methods, especially exploiting mass spectrometry, are moving breath analysis towards the clinical setting; some trace gas metabolites are already being exploited in diagnosis and therapy. Much effort is being given to the search for biomarkers of tumours in the body. HCN as an indicator of the presence of Pseudomonas in the airways has real potential in therapeutically alleviating the symptoms of cystic fibrosis.
Keywords: dýchací soustava; Ammonia; vodík; Volatile Organic Compounds; stopové prvky; Acetone; Trace Elements; Health Status; Nutritional Status; lidé; zdravotní stav; Breath Tests; kyanovodík; Carbon Dioxide; hmotnostní spektrometrie; nutriční stav; Hydrogen Cyanide; Hydrogen; oxid uhličitý; Mass Spectrometry; aceton; dechové testy; těkavé organické sloučeniny; amoniak; Respiratory System; Humans